Perbandingan Efektivitas Paracetamol vs Ibuprofen dalam Manajemen Demam Dewasa: Analisis Berbasis Data Real-World - Nur Amalinda; Haryanto Haryanto (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Fever is the body's response to infection or inflammation, which often indicates a certain medical condition. One common treatment for fever is the use of antipyretic drugs. The purpose of this study was to evaluate the effectiveness of antipyretic drugs in lowering body temperature in adult patients with fever. The method used was a clinical trial with a randomized controlled trial (RCT) design, involving 100 adult patients with fever ≥38°C. Patients were divided into two groups: the group receiving antipyretic drugs (paracetamol) and the placebo group. Body temperature measurements were taken every 2 hours for 24 hours after drug administration. The results showed that the group receiving antipyretic drugs experienced a significant decrease in body temperature compared to the placebo group (p <0.05). The side effects that appeared were relatively mild and not dangerous..